2008
DOI: 10.1016/j.worlddev.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Do the Asian Drivers Undermine Export-oriented Industrialization in SSA?

Abstract: Summary. -An increase in outward orientation in general, and in export-oriented manufacturing in particular is widely indicated as a suitable developmental path for SSA. The logic for this is drawn both from the demonstration effect of China and the earlier generation of Asian NICs, and from theory. However, the entry of China (and to a lesser extent India) into the global economy as a significant exporter of manufactures poses severe problems for export-oriented growth in SSA. This can be seen from SSA's rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 13 publications
1
92
0
Order By: Relevance
“…Utilising econometric analysis they compute a significant displacement effect in the US and European Union (EU) markets. This accords with other analyses of China-Africa trade relations (Kaplinsky and Morris, 2008). However, they take the argument further by also showing the growing displacement by China of African producers in intra-regional trade.…”
supporting
confidence: 87%
“…Utilising econometric analysis they compute a significant displacement effect in the US and European Union (EU) markets. This accords with other analyses of China-Africa trade relations (Kaplinsky and Morris, 2008). However, they take the argument further by also showing the growing displacement by China of African producers in intra-regional trade.…”
supporting
confidence: 87%
“…For example, Kaplinsky and Morris (2008) assert that the dominance of China in sectors such as textiles and clothing that serve traditionally as early sectors for industrialization not only precludes gains by other emerging countries but shuts down opportunities for less-developed countries even thinking about embarking on an exportled growth strategy in these sectors. Indeed, our results show that China's dominance in textiles (now a fifth of total Chinese exports) is due in large part to the contribution of non-price factors.…”
Section: Empirical Results For Exports Of Emerging Countriesmentioning
confidence: 99%
“…They have used various methods, including inspection of trade data (e.g. Lall et al 2005;Mesquita Moreira, 2007;Kaplinsky and Morris, 2008), revealed comparative advantage calculations (Lederman et al, 2008), gravity models (e.g. Greenaway et al, 2008;Hanson and Robertson, 2010) and computable general equilibrium (CGE) models (e.g.…”
Section: Introductionmentioning
confidence: 99%